Early Diagnosis and Results of Enzyme Replacement Therapy in the Patient with Mucopolysaccharidosis Type VI: Clinical Case - Dmitry V. Ivanov; Anna I. Ostrun; Vladimir M. Kenis; Tatiana V. Markova; Ekaterina Yu. Zakharova (Вопросы современной педиатрии)
Background. Mucopolysaccharidosis type VI (MPS VI, Maroteaux–Lamy syndrome) is rare autosomal-recessive multisystem disease, one of the group of lysosomal storage diseases. The MPS VI pathogenesis is determined by arylsulfatase B enzyme deficiency caused by mutations in the ARSB gene. There are only few published clinical examples of this disease that covers the results of early enzyme replacement therapy (ERT) onset.Clinical case description. The child was suspected to have lysosomal storage disease at the age of 1.5 months, it was based on microscopic analysis of blood smears: Alder abnormality was revealed (granulations and red-violet inclusions in neutrophils, monocytes, lymphocytes cytoplasm). The diagnosis was confirmed at the age of 3 months: increased glycosaminoglycans (GAGs) concentration in the urine, arylsulfatase B activity decrease in dried blood spots, and pathogenic variant c.943C>T (p. R315X) in the ARSB gene in homozygous state were revealed. ERT with galsulfase was started at the age of 7 months. There was decrease in excretion of GAGs in urine to normal level after 9 and 15 months of therapy. Normal growth and body proportions for the patient’s age were determined 3 years after continuous ERT. However, there was progression of multiple dysostosis and joint stiffness, as well as eyes lesion.Conclusion. Early ERT onset cannot completely stop MPS VI progression but it allows to reduce the severity of several symptoms and improves patient’s quality of life.